Evaluation of the safety and functional effects of recombinant humanized type III collagen in food toxicology - Zhang, Zhiyu; Yang, Wenqing; Yang, Jingbo; Lan, Xiaobin; Chen, Chuanxiu (Frontiers in Medicine, 2026)
This study aimed to comprehensively assess the edible safety and in vivo bioactivities of recombinant humanized type III collagen (rhCol III). A systematic toxicological evaluation was conducted, including subchronic toxicity tests, bacterial reverse mutation assays, mammalian erythrocyte micronucleus tests, and chromosome aberration tests. Concurrently, efficacy was evaluated using a zebrafish model to investigate multiple biological endpoints. The safety assessment revealed no toxicologically significant abnormalities, confirming a favorable safety profile for long-term oral consumption. In the zebrafish model, rhCol III significantly inhibited the expression of inflammatory factors, reduced the accumulation of advanced glycation end products (AGEs), alleviated oxidative stress damage, and improved molecular indicators associated with skin barrier function. The results demonstrate that rhCol III possesses multifaceted bioactivities, including anti-inflammatory, anti-glycation, antioxidant, and anti-aging properties. This research provides a robust scientific foundation for the development and application of rhCol III in high-value-added oral nutricosmetic products.